2006
DOI: 10.1124/mol.106.026294
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mouse Hepatic α-Amino-β-Carboxymuconate-ϵ-Semialdehyde Decarboxylase, a Key Enzyme in the Tryptophan-Nicotinamide Adenine Dinucleotide Pathway, by Hepatocyte Nuclear Factor 4α and Peroxisome Proliferator-Activated Receptor α

Abstract: Nicotinamide adenine dinucleotide (NAD) plays a critical role in the maintenance of cellular energy homeostasis. ␣-Amino-␤-carboxymuconate--semialdehyde decarboxylase (ACMSD) is the key enzyme regulating de novo synthesis of NAD from L-tryptophan (Trp), designated the Trp-NAD pathway. Acmsd gene expression was found to be under the control of both hepatocyte nuclear factor 4␣ (HNF4␣) and peroxisome proliferator-activated receptor ␣ (PPAR␣). Constitutive expression of ACMSD mRNA levels were governed by HNF4␣ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
(52 reference statements)
1
33
0
3
Order By: Relevance
“…Differentially expressed genes associated with a functional network related to AA and lipid metabolism were identified, which revealed that PPARa regulates proteins involved in AA metabolism, and this may occur indirectly, mediated through HNF4a. Previous studies have reported the established ability of PPARa to down-regulate the expression of HNF4a (Hertz et al 1995(Hertz et al , 1996Marrapodi and Chiang 2000;Shin et al 2006) and demonstrated an association between HNF4a and the expression of some AACE (Nitsch et al 1993;Odom et al 2004;Shin et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Differentially expressed genes associated with a functional network related to AA and lipid metabolism were identified, which revealed that PPARa regulates proteins involved in AA metabolism, and this may occur indirectly, mediated through HNF4a. Previous studies have reported the established ability of PPARa to down-regulate the expression of HNF4a (Hertz et al 1995(Hertz et al , 1996Marrapodi and Chiang 2000;Shin et al 2006) and demonstrated an association between HNF4a and the expression of some AACE (Nitsch et al 1993;Odom et al 2004;Shin et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…It has only recently been reported that PPs including fibrates down-regulated the expression of hepatic ACMSD mRNA in mice, and it was also demonstrated by using hepatic PPAR-null mice and HNF4-null mice that the constitutive expression of ACMSD mRNA was positively controlled by HNF4 and down-regulated by the activation of PPAR. 14) We have also reported that the downregulation of rat hepatic ACMSD mRNA caused by polyunsaturated fatty acids was not mediated by a PPAR-dependent pathway, although down-regulation by peroxisome proliferators was PPAR-dependent. 15) Our initial studies showed that rats fed with a phytol diet had an increased level of NAD in the blood, and decreased hepatic ACMSD activity, this occurring in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Moreover, fibrate affects the hepatic ACMSD gene expression via PPAR activation. 14,15) However, only a few studies have reported the effect of dietary phytochemicals on ACMSD expression in vivo and in vitro.…”
mentioning
confidence: 99%
“…NAM clearance metabolites have recently been proposed as potential biomarkers of peroxisome proliferator-activated receptor-a activation by fibrates (Delaney et al, 2005;Zhen et al, 2007). The large increase in NAM metabolites has been attributed to the suppression of the enzyme a-amino-b-carboxymuconate-«-semialdehyde decarboxylase by peroxisome proliferator-activated receptor-a, which increases the tryptophan flux through the quinolinic-nicotinamide adenine dinucleotide pathway, giving rise eventually to NAM clearance products (Sanada, 1985;Fukuoka et al, 2002;Shin et al, 2006). Our results suggest that NAM N-oxide might actually be a more direct biomarker of CYP2E1 provided that it shows the required specificity and correlation with CYP2E1 activity.…”
Section: Discussionmentioning
confidence: 99%